Analysis of Sharia Investment Gallery's Innovative Strategy in Increasing Millennial Investors' Interests Through AS-SALAM Programs - Zuana , Muhammad Mujtaba Mitra; Toha , Mohamad; Zamroni , M. Alif (LPPPM STAI Darul Hikmah Bangkalan, 2020)
Sharia capital market is a capital market that is related to its activities, regarding issuers, types of securities traded and their trading mechanism conducted based on sharia principles. UINSA Sharia Investment Gallery and UINSA Sharia Trash Bank collaborating to spark AS-SALAM investment products. The AS-SALAM product is a form of investment product for saving capital junk stocks. This research aims to study the innovative strategies adopted by GIS in increasing millennial investors’ interests through the AS-SALAM program. The method used in this research is descriptive method through qualitative research. The results of this study indicate how saving capital stock can increase the interests of millennial investors to start learning to invest. This is because the price of shares is low compared to shares on the outside and only with garbage.